Керамічні світильники Києва - Сергеєва, М.С. (Археологія, 1995)
У роботі розглядаються різні типи керамічних давньоруських світильників, їх датування, походження і подальша еволюція. В статье выделяются следующие типы светильников: светильники-мисочки нескольких видов, открытые одно- и двухярусные и светильники закрытого типа. Светильники-мисочки — самые ранние из них, приблизительно в XI в. появляются одноярусные и закрытого типа и только к началу XII в.— двухярусные. Последние получают широкое распространение только к середине — второй половине XII в. Светильники-мисочки формируются на основе местной керамики, прототипом одно- и двухярусных светильников могли быть византийские (причерноморские) люстроны, однако непосредственное развитие форм идет уже на древнерусской почве. Древнерусские светильники легли в основу позднесредневековых форм керамических осветительных приборов. The following types of lamps are described in the paper: lamps as bowls of several types, open one- and two-stage lamps and closed lamps. Lamps-bowls are the earliest, one-stage and closed lamps appeared somewhere in the 11th cent., and two-stage lamps appeared by the beginning of the 12th cent. The two-stage lamps have found wide distribution only in the mid-second half of the 12th cent. Lamps-bowls were made on the basis of native pottery, while a prototype of one- and two-stage lamps might be taken in Byzantine (Byzantine or Black-Sea chandeliers), though their further development proceeded the old-Russian way. The old-Russian lamps described have underlain late-medieval forms of ceramic lamps.